ANALISIS IMPLEMENTASI SAK- ETAP TERHADAP PENYAJIAN LAPORAN KEUANGAN PERUSAHAAN KONSTRUKSI PADA CV.AIRLANGGA - Safiera, Ratu Afifa (Undergraduate Program in Accounting, Department of Accounting, Faculty of Economics and Business, Universitas Tanjungpura, 2023)
ABSTRACTThe SAK-ETAP financial report is a financial report that can be used by entities without public accountability. Entity refers to an institution, organization, or business entity. It is called an entity without public accountability if the entity does not have significant public accountability and only publishes financial reports for general purposes for external users. SAK-ETAP financial reports can provide information on the financial position, financial performance and cash flow reports of an entity which is useful for certain users in making economic decisions. The object of this research is CV.Airlangga which operates in the field of civil and building construction services. The aim of the research is to determine the suitability between the financial reports prepared by CV.Airlangga and the financial reports based on SAK-ETAP. This research is qualitative research and the data collection techniques used are observation, interviews, documentation and literature study methods. The results of the research conducted concluded that CV.Airlangga's financial reports had not implemented SAK-ETAP in presenting its financial reports. CV.Airlangga only presents 2 financial reports, namely the balance sheet and profit and loss, while according to SAK-ETAP there are 5 components in presenting financial reports, namely the balance sheet, profit and loss report, capital changes report, cash flow report and financial statement flow notes. The obstacles faced by CV. Airlngga in implementing SAK-ETAP are a lack of socialization regarding the importance of implementing SAK-ETAP for companies, a lack of human resources who have the ability to prepare financial reports based on SAK-ETAP, weak supervision from interested parties regarding financial reports.